1985
DOI: 10.1002/1098-108x(198511)4:4<465::aid-eat2260040407>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural influences on eating disorders in professional female ballet dancers

Abstract: Fifty‐five white and eleven black female dancers in nine regional and national ballet companies in America and Europe (mean age 24.9) were surveyed for eating disorders. The dancers, as a whole, weighed 12% below their ideal weight for height. None of the black American dancers reported anorexia nervosa or bulimia, while 15% of the white American dancers reported anorexia nervosa and 19% reported bulimia. All instances of anorexia nervosa were in national rather than regional companies, making the incidence am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

1986
1986
2002
2002

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 21 publications
2
36
0
2
Order By: Relevance
“…Other researchers have similarly concluded that BN may be the result of the incorporation of cultural standards regarding thinness, hence the apparent relationship between these variables (Wiederman and Pryor 2000). Even though eating disorders were once thought to be predominantly a white upper-middle-class disorder (Hamilton, Brooks-Gunn, and Warren 1985), the present study demonstrated that Hispanics and Anglos are similar in their dissatisfaction with their body size, in their desire to be thinner, and in the extent to which they report symptoms of bulimia nervosa.…”
Section: Discussionsupporting
confidence: 53%
“…Other researchers have similarly concluded that BN may be the result of the incorporation of cultural standards regarding thinness, hence the apparent relationship between these variables (Wiederman and Pryor 2000). Even though eating disorders were once thought to be predominantly a white upper-middle-class disorder (Hamilton, Brooks-Gunn, and Warren 1985), the present study demonstrated that Hispanics and Anglos are similar in their dissatisfaction with their body size, in their desire to be thinner, and in the extent to which they report symptoms of bulimia nervosa.…”
Section: Discussionsupporting
confidence: 53%
“…Although numerous studies have attempted to identify the prevalence of anorexia nervosa and bulimia nervosa in female athletes (13,27,31,36,40,45,46,56,67,74,83,84,99), to date few studies have specifically or deliberately examined the prevalence of subclinical eating disorders (33,73,83). Anecdotal reports and research providing indirect evidence, however, seem to suggest that the incidence of subclinical eating disorders in female athletes is quite high, particularly among those participating in sports that require a low body weight (12,15,22,27,40,58,64,73,81).…”
Section: Prevalence Of Subclinical Eating Disordersmentioning
confidence: 99%
“…Baixo peso e má nutrição são fatores importantes na determinação do início da desmineralização na presença de amenorréia. A incidência de anorexia nervosa em bailarinas varia de 5 a 22% (37). O relacionamento entre exercício e DMA é complexo e incompletamente esclarecido.…”
Section: Tríade Da Mulher Atletaunclassified